Pathomorphology of the placenta in COVID-19 infection - E.F. Pchelnikova; V.N. Brinkevich; V.S. Ogrizko; V.A. Ignatovich; Ya.A. Govorushkina (Вестник Витебского государственного медицинского университета, 2022)
The aim of the study was to identify and describe histopathological findings during microscopic examination of the placenta preparations of women infected with the SARS-CoV-2 virus using the International Classification of Placental Lesions. The results of macro- and microscopic examination of the placentas of 53 patients with confirmed infection with the SARS-CoV-2 virus were analyzed. The following observation groups were identified: Group I – 22 women who had recovered from a viral infection by the time of admission to the hospital; Group II – 27 women with mild or asymptomatic COVID-19 (PCR+); Group III – 4 women with moderate and severe form of infection course. Information about the nature of delivery, gestational age, as well as the weight of the placenta, changes in the umbilical cord and microscopic examination data of the placenta were analyzed. As a result of using the “International Classification of Placental Lesions” criteria, the data obtained revealed the greatest pathomorphological changes in the form of damage to the stromal-vascular component and inflammatory-immune processes, both on the part of the mother’s body and the fetus. The nature and severity of these changes were determined by the severity of the coronavirus infection. The results of the work clarify the general ideas about the effects of COVID-19 observed during the epidemic on the course of pregnancy, placental pathology, and perinatal outcomes. The results of the conducted study can be used in obstetric practice as an objective reason for strengthening prenatal monitoring of pregnant women with the diagnosis of SARS-CoV-2.